Boosting the electrochemical performance of MoO3 anode for long-life lithium ion batteries: Dominated by an ultrathin TiO2 passivation layer. (10th April 2018) - Cheng, Xiaopeng; Li, Yonghe; Sang, Lijun; Ma, Jinyao; Shi, Huifeng; Liu, Xianqiang; Lu, Junxia; Zhang, Yuefei
Abstract: In this report, using atomic layer deposition (ALD) technique, TiO2 layer with different thickness is conformally deposited on the surface of MoO3 nanobelts for enhanced-performance anode. Impressively, the MoO3 @85-TiO2 (85 cycles coating) nanobelts anode shows its best comprehensive value: The initial Coulombic efficiency (CE) dramatically increases from 44% to 73% compared to bare MoO3 electrode; It also delivers highest initial specific capacity of 1153.7 mAh g −1 at 100 mA g −1, which is superior to the uncoated MoO3 (427.3 mAh g −1 ). Additionally, MoO3 @85-TiO2 nanobelts show a remarkable long-life stability from initial 913.6 to 935.8 mAh g −1 after 400 charge-discharge cycles at 400 mA g −1 . The advanced TEM characterizations reveal that the TiO2 layer can experience a transition from amorphous into crystalline Li2 Ti2 O4 with cubic structure (a = 8.375 Å) during cycling, which are acted as an efficient lithium ion conductor. Furthermore, the quantified mechanical properties demonstrate a remarkable decrease in the bending elastic modulus of MoO3 @85-TiO2 nanobelts compared to that of pristine MoO3 . Therefore, the boosted electrochemical performance can be attributed to efficient lithium ions transportation across the moderate conductor layer and robust mechanical integrity that the large volume variation. These results advance the understanding in the coating regulated materials for enhanced-performance LIBs. Graphical abstract: In this work, amorphous TiO2 layer with different thickness (sub 10 nm) is homogenously coated MoO3 nanobelts by atomic layer deposition method. As an anode for LIBs, compared to the bare MoO3 nanobelts, the MoO3 @85 cycles TiO2 nanobelts show a remarkable boosted capacitance and long-life stability, which is attributed to the high interfacial Li + transport paths and mechanical integrity regulated by the ultrathin layer. Highlights: MoO3 nanobelts are precisely coated with amorphous TiO2 via ALD method. Optimized thickness of TiO2 with ∼ 3 nm was obtained (ALD 85 cycles). The MoO3 @85 cycles TiO2 nanobelts show boosted capacitance and long-life stability. Boosting the capacity is attributed to the efficient Li + transport paths. The TiO2 buffer layer modification accommodate the repeated volume expansion.